Structuralism - Richard Smith (International Encyclopedia of Human Geography, 2019)
Structuralism is a philosophy and method that developed from insights in the field of linguistics in the mid-twentieth century to study the underlying patterns of social life. In the social sciences the structuralist mode of inquiry sought not simply to identify structures or relationships per se, but rather to look behind or beneath the visible and conscious designs (beliefs, ideas, behaviors) of active human subjects (surface manifestations) to expose or unearth how those designs are in fact outputs, effects, consequences, products generated by underlying causes, hidden mechanisms, or a limited number of ‘deep’ structures that are universal to the human mind. The structuralist approach was invented and developed by several key thinkers – e.g. Saussure, Lévi-Strauss, Lacan, Barthes, Foucault – and many others across several disciplines. However, lacking a champion for structuralism in human geography structuralism only entered Anglophone human geography in the early 1970s in a very limited way so that structuralism is primarily only relevant and important in contemporary human geography because of the traces it has left in the philosophical movements it spawned: namely, deconstruction and the many other poststructuralisms that now command so much attention in human geography.